Perendaman Serat Batang Aren dengan NaOH sebagai Substrat Hidroponik Cabai Merah Besar - Yulfa Astuti Ika Sari; Dwi Harjoko; Retna Bandriyati Arniputri (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
NaOH treatment is expected to can increased fiber tensile strength, therefore it is to become stronger and durable as substrate on hydroponic. This research aimed to study the growth and yield responses of chili, also fiber characteristic due to NaOH soaking treatment. This research was conducted on December 2018 to July 2019 at Greenhouse B and Laboratory of Plant Physiology and Biotechnology, Faculty of Agriculture, Universitas Sebelas Maret. This method used was Completely Randomized Design (CRD) that consisted of 2 factors and 3 replications. The first factor was NaOH concentration which consists 6 levels; 0%, 1%, 2%, 3%, 4% and 5%. The second factor was soaking duration which consists 4 levels; 0, 2, 4 and 8 hours. The results showed that NaOH treatment increased pH, bulk density, particle density and water holding capacity, however it is decreased macro pores on fiber. Treatment of 5% NaOH with 2 hours soaking duration decreased percent of fiber decomposed. Arenga wood fiber soaked on 2 hours duration increased root length. NaOH treatment decreased the number of fruits, weight fruit and weight of dried plant biomass, however treatment of 5% NaOH increased vitamin C content on fruit.